Analisis Pengaruh Kemudahan Akses, Persepsi Kemanfaatan, Dan Financial Literacy terhadap Pengguna Paylater Oleh Gen Z Di Surakarta - Abigail Audry Koes Hardania; Dianing Widya Kusumastuti (AKUNTANSI 45, 2026)
The research seeks to examine how accessibility, perceived benefits, and financial knowledge influence Generation Z’s choices in adopting the Paylater option within digital wallet apps in Surakarta. It adopts a quantitative methodology featuring a causal associative framework. Key information was gathered via internet-based surveys sent to 100 participants chosen through purposive sampling techniques. Statistical examination involved multiple linear regression analysis utilizing SPSS software. Findings reveal that accessibility and perceived benefits exert a positive and meaningful impact on decisions to employ Paylater, whereas Financial Literacy demonstrates a negative and substantial influence. In essence, enhanced ease of use and greater recognized advantages boost the likelihood of opting for this feature, but elevated financial awareness diminishes interest due to heightened recognition of associated monetary hazards. These outcomes bolster the relevance of the Theory of Planned Behavior in interpreting behaviors related to electronic finance. On a practical level, the insights urge providers of digital financial solutions to harmonize user-friendly innovations with initiatives in financial education to encourage more accountable engagement with Paylater offerings.